The effect of thioredoxin‐1 in a rat model of traumatic brain injury depending on diurnal variation - Roxana Noriega‐Navarro; Ricardo Jesús Martínez‐Tapia; Rubén González‐Rivera; Alicia Ochoa‐Sánchez; Julio César Abarca‐Magaña; Lucía Landa‐Navarro; Verónica Rodríguez‐Mata; Perla Ugalde‐Muñiz; Armando Pérez‐Torres; Abraham Landa; Luz Navarro (Brain and Behavior, 2023)
Abstract Introduction Traumatic brain injury (TBI) is a public health concern with limited treatment options because it causes a cascade of side effects that are the leading cause of hospital death. Thioredoxin is an enzyme with neuroprotective properties such as antioxidant, antiapoptotic, immune response modulator, and neurogenic, among others; it has been considered a therapeutic target for treating many disorders. Methods The controlled cortical impact (CCI) model was used to assess the effect of recombinant human thioredoxin 1 (rhTrx1) (1 μg/2 μL, intracortical) on rats subjected to TBI at two different times of the light‐dark cycle (01:00 and 13:00 h). We analyzed the food intake, body weight loss, motor coordination, pain perception, and histology in specific hippocampus (CA1, CA2, CA3, and Dental Gyrus) and striatum (caudate‐putamen) areas. Results Body weight loss, reduced food intake, spontaneous pain, motor impairment, and neuronal damage in specific hippocampus and striatum regions are more evident in rats subjected to TBI in the light phase than in the dark phase of the cycle and in groups that did not receive rhTrx1 or minocycline (as positive control). Three days after TBI, there is a recovery in body weight, food intake, motor impairment, and pain, which is more pronounced in the rats subjected to TBI at the dark phase of the cycle and those that received rhTrx1 or minocycline. Conclusions Knowing the time of day a TBI occurs in connection to the neuroprotective mechanisms of the immune response in diurnal variation and the usage of the Trx1 protein might have a beneficial therapeutic impact in promoting quick recovery after a TBI.